Antidiabetic Activity of Momordica charantia L. and Mechanism of Insulin Secretion of 1-Butanol Soluble Part on Type 2 Diabetic Model Rats (Dhaka University Journal of Pharmaceutical Sciences, 2020)
The in vivo effects of fruit pulp juice (MC-PJ) of Momordica charantia and its 1-butanol soluble part (MC-BP) and aqueous soluble part (MC-AP) on blood glucose of type 2 diabetic rats were studied. In vitro insulin secretion in response to MC-BP and MC-AP from whole perfused pancreas was measured. For elucidating the mechanism of insulinotropic action, the insulin secretory activity of MC-BP in the presence of 11 mM glucose, 50 μM verapamil (Ca++ channel blocker), 8 mM diazoxide (K+ ATP channel opener) and 10 mM theophylline (cAMP phosphodiesterase inhibitor) were studied. Serum glucose was measured by glucose oxidase-peroxidase method and rat insulin was assayed by specific ELISA. In the in vivo study, MC-BP significantly opposed the rise of serum glucose compared to control at 105 min (p